Film Premiere Center : "Estreno La Pelicula Central" - Dela Paz, Patrick Kite S. J. (Manila : National University, 2015)
Movies are powerful force in Philippines society. It is more than just a source of entertainment, but also reflects the nation's personality.
Title page -- Approval sheet -- Acknowledgement -- Abstract -- Chapter 1. The problem and its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of references -- Chapter 4. Data gathering, collation and analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Suggestions, corrections & Final revisions -- Annexes.
Includes bibliographical references.
Keywords: CENTER -- PLANNING; FILM CENTER